Pengaruh Kompensasi dan Iklim Organisasi terhadap Kinerja Guru - Sugeng, Sugeng (Universitas muhammadiyah palembang, 2019)
This research aims to examine the factors which affect Teacher Performance consists of Compensation and Organizational Climate at SMAIT DEF, Sawangan - Depok.This research is causality using quantitative approach. Variables used are two variables, those are independent variables which Compensation (X1) and Organizational Climate (X2) with dependent variables is Teacher Performance (Y). The population in this research includes all teacher who work in SMAIT DEF. The sample technique used by total sampling as many as 30 respondents. The analytical tool used is multiple linear regression.According to the research result, find: (1) Compensation and Organizational Climate simultaneously have positive and significant effects to Teacher Performance in SMAIT DEF, Sawangan - Depok; (2) Compensation has no significant effect to the Teacher Performance while Organizational Climate has significant effect to the Teacher Performance